Quantification of information transmission in signal play-calling for NCAA Division 1 college football: a comprehensive literature review - King, M. E.; Miller, S.; Reimann, W.; Shalala, J.; Piroli, A.; Bichey, C.; Rath, T. (International Journal of Kinesiology & Sports Science, 2022)
Background: To gain a competitive advantage in National Collegiate Athletic Association (NCAA) Division 1 American college football, teams often use a coded, hand/body gesture-based play-calling system to communicate calls to student-athletes on the field. Objective: The purpose of this study is to apply cognitive engineering concepts toward the improvement of signal transmission such that a realistic amount of data signaled will be received and understood by the student-athlete. Methods: Partnering with an NCAA coaching staff, information transmitted via signal-based communication pathways were quantified to inform the design of their signal system. Quality control coaches, practitioners of football signalling characterization and design, used an autoethnographic frame to train researchers on the communication protocol standards. A comprehensive literature review of sources from 1900 to 2019 was conducted to examine information transmission, signal-gesture taxonomies, sign-language recognition, and code design. Findings were applied to the signal system to quantify the information contained in the transmission between the signalling coaches and the student-athletes. Results: Results found that the observed signal system transmits an average of 12.62 bits of information on offense and 12.92 bits on defense with 23% and 12% redundancy, respectively. Conclusion: Recommendations were provided to the coaching staff regarding code optimization and gesture design to improve student-athlete performance.